Anti-bacterial PES-cellulose composite spheres: dual character toward extraction and catalytic reduction of nitrophenol. Issue 111 (18th November 2016) - Khan, Sher Bahadar; Khan, Shahid Ali; Marwani, Hadi M.; Bakhsh, Esraa M.; Anwar, Yasir; Kamal, Tahseen; Asiri, Abdullah M.; Akhtar, Kalsoom
Abstract : Polyethersulfone (PES) based hybrid adsorbents were used for the removal of different phenols from aqueous solutions, which are categorized as major aquatic organic pollutants. Abstract : Polyethersulfone (PES) based hybrid adsorbents were used for the removal of different phenols from aqueous solutions, which are categorized as major aquatic organic pollutants. In an effort to develop adsorbents with high surface area, PES, PES-silica (PES-SiO2 ), PES-carbon black (PES-CB) and PES-cellulose acetate-CB (PES-CA-CB) were prepared in the form of spheres and characterized by using FESEM, TEM, EDS, XRD, FTIR, and TGA. All the hybrid spheres were selective toward adsorption of 4-nitrophenol (4-NP) and among different hybrid spheres, PES-CA-CB spheres possessed high affinity and competent selectivity toward 4-NP. Therefore, different adsorption parameters have been optimized for PES-CA-CB spheres. The adsorption uptake of 4-NP onto PES-CA-CB spheres was highly dependent on pH and concentration of 4-NP. The highest adsorption was recognized at a pH around 6. The adsorption isotherm of 4-nitrophenol on PES-CA-CB obeyed the Langmuir model with an adsorption capacity of 128.79 mg g −1 . Further, all hybrid spheres were utilized as supporting materials for Cu nanoparticles. Hybrid spheres supported Cu nanoparticles were applied for the catalytic reduction of 4-NP. Among all the hybrid spheres supported Cu nanoparticles, PES-CA-CB spheres supported Cu (Cu@PES-CA-CBspheres ) nanoparticles exhibited high catalytic activity. Finally, Cu@PES-CA-CBspheres showed excellent antibacterial activity compared to all the hybrid spheres and hybrid spheres supporting Cu nanoparticles. All these adsorbents and catalysts can be prepared by a very simple method, are easily recovered by just removing the pellet from the solution and can be used several times.